Successful surgical management of an aorto-oesophageal fistula caused by button battery ingestion. (28th August 2018) - Mahajan, Sachin; Jaswal, Vivek; Thingnam, Shyam Kumar Singh; Dogra, Neeti
Abstract: Aorto-oesophageal fistula is a rare complication of foreign body ingestion from which few patients survive. Aggressive surgical treatment is the only form of effective therapy for this fatal complication. We present the successful surgical treatment of an aorto-oesophageal fistula in a child without using cardiopulmonary bypass.